Effects of variation in air conditioner temperature on small airway functions of air conditioner users: AC temperature and small airway function - Chakrabarty, Swarnali; Akhter, Qazi Shamima (Journal of the Medical College for Women & Hospital, 2024)
Background:Increasing use of air conditioner(AC) has now become a new public health concern as the lung functions can be adversely affected by the cold, dry air provided by it or to be more specific by the sudden temperature change experienced by AC users . AC temperature may play an important part in this regard as more the difference between indoor and outdoor air temperature more could be the chance of this harmful consequences . Aim:This study particularly addressed this issue of how AC temperature variation can affect Mid Maximal Flow Rate (MMEF) value. Materials and Method:Individuals having exposure to daily air conditioned environment for at least 6 hours for 2 to 4 years were recruited following their provision of informed consent in written format. Forty eight such participants (24 female and 24 male) were distributed into 2 groups , A1 (12 female and 12 male subjects) and A2 (12 female and 12 male subjects)depending on the temperature of the AC they were having exposure of. The A1 group had exposure to temperature of 18° C to 22°C while A2 experienced temperature of 23°C to 25°C for a certain period of time. In both of these groups MMEF was estimated using digital autospirometer. Unpaired Student’s ‘t’ test was applied performing statistical analysis and p value 0.05 was taken as the level of significance. Result:This study displayed significantly lower MFF value for group A1 subjects in comparison to group A2.Conclusion: So, this study concludes that reduction of MMEF value in AC users may be related to the AC temperature to which they are exposed J Med Coll Women Hosp. 2024; 20(2):17-22